Aluna: A Student Management System For Tuition Uni Pintar - Sofian, Safwan; Saringat, Mohd Zainuri (Applied Information Technology And Computer Science, 2023)
The web-based Student Management System for Tuition Uni Pintar enhances the efficiency of existing manual processes by implementing a structured and systematic approach. Developed for teachers and students, Aluna replaces the conventional paper-based information storage with a robust system. Employing the Evolutionary Prototyping Model, the system utilizes software such as HTML, PHP, Java, JS, Visual Code, and a MySQL server for data storage. The implementation of Aluna optimizes the tuition center’s operations, providing better systematic management and improving teacher efficiency. Accessible through laptops or computers, the system enables teachers to manage student information seamlessly. This report highlights the features and benefits of Aluna, emphasizing its potential to revolutionize tuition center management and enhance productivity.